Economic Performance of MSMEs in Medan City: An Evaluation of the E-Catalog Government Policy's Effectiveness - Muhammad Rifqi Akbar; Tri Inda Fadhila Rahma; Nurul Jannah (Yayasan Riset dan Pengembangan Intelektual, 2023)
The Mayor of Medan has launched a policy that fulfills the consumption sector for all activities within the Medan City Government to promote Micro, Small and Medium Enterprises (MSMEs). There are many efforts made by the Medan city government to raise MSMEs in this region. Starting from carrying out many regional events, UMKM bazaars, to the needs in the office area itself using vendors from MSMEs. The research uses a qualitative descriptive method. In this methodology, researchers emphasize the socially constructed nature of reality, the close relationship between the researcher and the subject under study. The data used in this study uses primary data obtained from direct interviews with the Medan City Government and MSME players related to the E-Catalog program to see how effective this system is in developing existing MSMEs. It is concluded that this e-catalog program has not fulfilled all aspects of the effectiveness of the theory. Where there are 5 theories of the effectiveness of the success of government programs that can be assessed from the success of the program, the success of the target, satisfaction with the program, the level of input and output, and the achievement of overall goals. However, the Medan City Government's program in advancing MSMEs should be appreciated, where this program has a huge impact on increasing MSME turnover and helping several MSMEs survive the Covid-19 pandemic.